Endothelial Activation: The Ang/Tie Axis in Sepsis - Leligdowicz, Aleksandra; Richard-Greenblatt, Melissa; Wright, Julie; Crowley, Valerie M.; Kain, Kevin C. (Frontiers in Immunology, 2018)
Sepsis, a dysregulated host response to infection that causes life-threatening organ dysfunction, is a highly heterogeneous syndrome with no specific treatment. Although sepsis can be caused by a wide variety of pathogenic organisms, endothelial dysfunction leading to vascular leak is a common mechanism of injury that contributes to the morbidity and mortality associated with the syndrome. Perturbations to the angiopoietin (Ang)/Tie2 axis cause endothelial cell activation and contribute to the pathogenesis of sepsis. In this review, we summarize how the Ang/Tie2 pathway is implicated in sepsis and describe its prognostic as well as therapeutic utility in life-threatening infections.